DETERMINATION OF DISPLACEMENT OF FIVE-STOREY BUILDING UNDER ACTION OF SEISMIC FORCES (Spectrum Journal of Innovation, Reforms and Development, 2023)
In this article, seismic forces affecting a five-story building were incorrectly distributed, as a result of incorrect placement, displacements were detected in the building. design works were performed in accordance with the current standard. general information about the construction site, geometric indicators of the building, dynamic characteristics of the building, strength and mechanical indicators of construction materials were taken from the location of the building and analyzed.